If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 6y + 20y + -13y = -19 Combine like terms: 6y + 20y = 26y Y + 26y + -13y = -19 Combine like terms: 26y + -13y = 13y Y + 13y = -19 Solving Y + 13y = -19 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-13y' to each side of the equation. Y + 13y + -13y = -19 + -13y Combine like terms: 13y + -13y = 0 Y + 0 = -19 + -13y Y = -19 + -13y Simplifying Y = -19 + -13y
| bk=1.5(7-k) | | 7x+12+9x-8= | | 0n-1n+4=2 | | (9l^2-3l-9)-(3l^2-8l+10)= | | 6x+2x+40=180 | | 6x^2-5+-21=0 | | 11m-7m-18m+20m=18 | | -x-14y=1 | | m^2-6m-73=0 | | 0n+-3n=13 | | 16x^2-25y^2-256x-150y+399=0 | | 7b-15=b+3 | | X=-3X-10 | | 2b^2+32b+128=0 | | 5y+1+3y=(-15) | | -2x-8y=-1 | | 2b(b+1)=4+2b^2 | | 9d-d-7d=11 | | 4x+4-2x= | | 7b^2+70b+63=0 | | -16t^2-192t=512 | | 18-3y=2x+-10 | | 6+3(z-2)=-3z+1 | | 2n(3n-1)=0 | | (4m)(5)+5(3m-2)= | | 10q-9q-q+4q-3q=20 | | 5+2n-3n=2 | | 11.3-4b=-4.7 | | 4b^2+16b+48=0 | | a^2+18+11a=0 | | 4x+1=7+2+8x-5 | | log[12](2m+7)=log[12](2-3m) |